Animal motifs on rock art in Papua and West Papua - Permana, R. Cecep Eka; Mas'ud, Zubair (UI Scholars Hub, 2023)
Most of the rock art in Indonesia is found at prehistoric sites, specifically caves or cliffs in South Sulawesi, Southeast Sulawesi, East Kalimantan, Maluku, Papua, and West Papua. Most rock art with animal motifs is mainly located in Papua and West Papua. Therefore, the data in this paper are mostly based on the results of research conducted during the last ten years at rock art sites in Papua Province (with hinterland and mountainous characteristics) and in West Papua Province (with coastal and archipelagic characteristics). An analysis of these animal motifs has demonstrated that lizard and fish motifs dominate rock art in these provinces. However, rock art in Papua and West Papua also depicts turtles, snakes, birds, and several types of marine animals. The depiction of animals in rock art in Papua and West Papua has generally been interpreted as ancestor worship. However, this research argues that the interpretation of animal motifs is also related to the ongoing communal concerns and traditions, such as the fertility of the fields, success in fulfilling daily needs, and healing diseases.